Speech and the Right Hemisphere - E. M. R. Critchley (Behavioural Neurology)
Two facts are well recognized: the location of the speech centre with respect to handedness and early brain damage, and the involvement of the right hemisphere in certain cognitive functions including verbal humour, metaphor interpretation, spatial reasoning and abstract concepts. The importance of the right hemisphere in speech is suggested by pathological studies, blood flow parameters and analysis of learning strategies. An insult to the right hemisphere following left hemisphere damage can affect residual language abilities and may activate non-propositional inner speech. The prosody of speech comprehension even more so than of speech production—identifying the voice, its affective components, gestural interpretation and monitoring one's own speech—may be an essentially right hemisphere task. Errors of a visuospatial type may occur in the learning process. Ease of learning by actors and when learning foreign languages is achieved by marrying speech with gesture and intonation, thereby adopting a right hemisphere strategy.